Infrastructure in the framework of production functions: evidence of EU member states at the regional level - Mačiulytė-Šniukienė, Alma; Butkus, Mindaugas; Szarucki, Marek (Technological and Economic Development of Economy, 2022)
Infrastructure development is seen as an essential tool for boosting economic growth. Infrastructure is funded under various programs to contribute to economic growth, and reduce regional disparities. Evaluations of the results achieved have to be carried out to develop efficient infrastructure development and investment allocation policy. This is highlighted in both the reports of policymakers and scientific publications. The main limitation of these studies is that they focus on assessing the return on infrastructure development at the national level, leaving the question of what outcomes were achieved at the regional level. This article aims to evaluate the economic outcomes of transport and ICT infrastructure development at the NUTS 2 regional level in the EU-28 countries, using 2000–2019 data. The research is based on the neoclassical production function complementing it with an infrastructure indicator. Based on previous research, it is hypothesized that economic outcomes may depend on the institutional environment of the region. Consequently, the research model specification is supplemented by government quality as a possible moderator. Research findings suggest just motorway and internet infrastructure are significantly positively related to production outcomes. Estimations show higher government quality and less corruption are related to the bigger production output of the infrastructure input.